Encounters in nonlinear optics : (World Scientific, 1996)
This selection of papers in the field of nonlinear optics contains reprints of original research, and general reviews written since 1960 up to the present. Brief comments by the author place each paper in a historical context of the evolution of nonlinear optics. Papers are selected from a more comprehensive bibliography either on the basis of their influence on subsequent developments or because they were originally published in journals or conference proceedings which are less easily accessible.